Scientific Imperialism: Economics Imperialism Against Sociology in Iran - Farhad Bayani (Richtmann Publishing, 2023)
The growing attention of the government in Iran to the individual-centered discourse and its knowledge kinds has caused a slow and increasing influence of individual-centered theories, methodologies and approaches (including economics, along with emerging psychology and mysticism) in social explanations and analysis, and this is one of the implications and examples of the imperialist relationship between individualist discourse and sociology. This article aims to investigate, examine, and expose the various facets of this scientific imperialism. Documentary research methodology is the foundation of this study. The underlying premise of this study is that the ontological and epistemological underpinnings of the Nominalism school, along with historical and empirical evidence to support them, play a vital role in the principles and foundations of economics (one of the definitions of individual-centred discourse). The results demonstrate that individualism and atomism, particularly in economics, have evolved and become more pervasive in Iranian culture. Nominalism has been crucial in theorising this scenario since it serves as the discourse's ontological and epistemic base. The result of this situation is nothing but the dominance of the individual-centered and the weakening of the social, both in the analysis of reality and in its construction. In the meantime, one should not and cannot ignore the relation and cooperation of power and knowledge for the emergence and stabilization of this situation. Received: 24 May 2023 / Accepted: 27 June 2023 / Published: 5 July 2023